2018
DOI: 10.3906/vet-1702-52
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stoned olive pomace on carcass characteristics and meat quality of lambs

Abstract: Thirty-six Merino-Kıvırcık crossbred male lambs were utilized to evaluate the influence of two levels of dried stoned olive pomace. Lambs were blocked by initial body weights (BW, 20.4 kg) and randomly distributed into three groups. While one group received commercial concentrates without olive pomace, the second and third groups received an experimental diet containing 10% olive pomace and 20% olive pomace, respectively. They were fed for 49 days. The animals' BW and feed consumption were recorded weekly and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The lack of differences (p = 0.251) between groups in the proportion C18:1 n-9 observed in our study agrees with the results of Kotsampasi et al [50], who did not observe differences in this FA in lambs fed destoned EOC, and it was attributed to both the low fat content of the EOC (2.91%, DM basis) and the low level of inclusion in the BYP concentrate (8%). In contrast, several studies have reported increases in the proportion of C18:1 n-9 in the meat of lambs by feeding crude olive cake [63,64]. In agreement with previous results in lambs fed high-concentrate diets [34,48,65], for both groups of lambs, the most abundant FA was (C18:1 n-9), followed by C16:0 and C18:0.…”
Section: Resultssupporting
confidence: 89%
“…The lack of differences (p = 0.251) between groups in the proportion C18:1 n-9 observed in our study agrees with the results of Kotsampasi et al [50], who did not observe differences in this FA in lambs fed destoned EOC, and it was attributed to both the low fat content of the EOC (2.91%, DM basis) and the low level of inclusion in the BYP concentrate (8%). In contrast, several studies have reported increases in the proportion of C18:1 n-9 in the meat of lambs by feeding crude olive cake [63,64]. In agreement with previous results in lambs fed high-concentrate diets [34,48,65], for both groups of lambs, the most abundant FA was (C18:1 n-9), followed by C16:0 and C18:0.…”
Section: Resultssupporting
confidence: 89%
“…Additionally, a large body of evidence indicated that the use of Olea europaea polyphenols in animal feed does not negatively affect other quality indicators (pH, cooking loss, and shear force, for instance) of meat obtained from lambs [95,[108][109][110][111], goats [77,96], rabbits [98,99], pigs [97,112], cattle [113], and chicken [100][101][102], in terms of chemical composition, pH, color, shear force, drip loss, cooking loss, or sensory properties. Collectively, Olea europaea polyphenols can improve the redox status of fresh meat during storage.…”
Section: Animal Feeding and Meat Qualitymentioning
confidence: 99%